1993
DOI: 10.2337/diacare.16.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Sialic Acid Concentration in NIDDM and Its Relationship to Blood Pressure and Retinopathy

Abstract: Total serum sialic acid levels were significantly elevated in a relatively small group of NIDDM patients and were correlated with hypertension and retinopathy. A larger study of circulating sialic acid concentrations as a risk factor for the development or marker of diabetic angiopathy is therefore justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 12 publications
7
68
1
1
Order By: Relevance
“…A relationship between serum or plasma sialic acid levels and microvascular complications has been observed before in small-scale studies for microalbuminuria and clinical proteinuria in type 1 (6,7) and type 2 diabetes (18), and for retinopathy in type 1 (19) and type 2 diabetes (20). An association with neuropathy has not been reported before.…”
Section: Conclusion -mentioning
confidence: 76%
“…A relationship between serum or plasma sialic acid levels and microvascular complications has been observed before in small-scale studies for microalbuminuria and clinical proteinuria in type 1 (6,7) and type 2 diabetes (18), and for retinopathy in type 1 (19) and type 2 diabetes (20). An association with neuropathy has not been reported before.…”
Section: Conclusion -mentioning
confidence: 76%
“…We showed, however, that concentrations of the acutephase marker, serum sialic acid, are raised in Type II diabetes, even in those without diabetic tissue complications, but are not altered in uncomplicated Type I diabetic subjects of similar age and glycaemic control to the Type II diabetic group [19,20].…”
Section: Evidence For An Acute-phase Response In Type II Diabetesmentioning
confidence: 67%
“…serum sialic acid is a marker of the acute-phase response (5,12), acute-phase glycoproteins with sialic acid as a component of the oligosaccharide side chain being produced by the liver, stimulated by pro inflammatory cytokines such as interleukin-1, interleukin-6, and tumor necrosis factor (13,14).So the present finding explains that tissue injury caused by diabetic vascular complications and endothelial dysfunction. Previous studies in NIDDM and IDDM with incipient nephropathy demonstrated increased serum total Sialicacid levels [15,16] which is claimed to be a strong predictor of cardiovascular mortality [11,17,18]. Serum total sialic acid was significantly increased in patients undergoing cardiopulmonary bypass, which is known to induce an inflammatory response [19] and correlated with inflammatory, but not ischaemic markers, following cross-clamp removal [20].And interestingly serum total sialic acid, total and LDL cholesterol were significantly decreased in growth hormone-deficient adults who were randomized to receive 3 months of growth hormone replacement therapy, compared to placebo therapy [21].…”
Section: Discussionmentioning
confidence: 99%
“…some prospective studies that have investigated the relation between sialic acid and risk of cardiovascular disease. An elevated serum concentration of sialic acid (N-acetylneuraminic acid) is a strong predictor in the general population of cardiovascular death [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%